2016
DOI: 10.1104/pp.16.00629
|View full text |Cite
|
Sign up to set email alerts
|

IRREGULAR POLLEN EXINE1 Is a Novel Factor in Anther Cuticle and Pollen Exine Formation

Abstract: ORCID IDs: 0000-0002-4656-3189 (H.S.); 0000-0003-0518-5924 (C.Z.); 0000-0001-9320-9628 (W.J.).Anther cuticle and pollen exine are protective barriers for pollen development and fertilization. Despite that several regulators have been identified for anther cuticle and pollen exine development in rice (Oryza sativa) and Arabidopsis (Arabidopsis thaliana), few genes have been characterized in maize (Zea mays) and the underlying regulatory mechanism remains elusive. Here, we report a novel male-sterile mutant in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 67 publications
3
78
0
Order By: Relevance
“…HOTHEAD ( HTH ) in Arabidopsis (Krolikowski et al ., ; Kurdyukov et al ., ) and ONI3 , the rice ortholog of HTH (Akiba et al ., ), affects cutin metabolism and organ genesis. The orthologous gene of NP1 in maize, IPE1 , is also involved in pollen exine and cuticle formation, suggesting a conserved role of NP1 and its orthologs in plant male reproduction (Chen et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…HOTHEAD ( HTH ) in Arabidopsis (Krolikowski et al ., ; Kurdyukov et al ., ) and ONI3 , the rice ortholog of HTH (Akiba et al ., ), affects cutin metabolism and organ genesis. The orthologous gene of NP1 in maize, IPE1 , is also involved in pollen exine and cuticle formation, suggesting a conserved role of NP1 and its orthologs in plant male reproduction (Chen et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Another Arabidopsis GMC superfamily member, At1 g12570, is the NP1 ortholog, inducible by cutin regulator WIN1/SHN1 and supposed to be involved in cutin biosynthesis (Kannangara et al ., ). A recent report indicates that At1g12570 has a partially conserved role in male reproductive development (Chen et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We can infer that retarded PCD triggers fatty acid metabolic abnormalities, which in turn compromises normal pollen maturity and leads to total male sterility in the 2–517 line. Based on previous cytological studies and biochemical analysis on sporopollenin and cuticle synthesis mutants, [ 62,63 ] we designed a biological synthesis model of the anther cuticle and pollen exine in the pollen maturation process ( Figure ). After being transferred into the endoplasmic reticulum, the middle‐and long‐chain fatty acids which are synthesized in plastids, will be ω‐hydroxylated by CYP704, a member of the CYP gene family.…”
Section: Discussionmentioning
confidence: 99%
“…These works also implicate the importance of arabinogalactan-protein in the construction of the pollen coat. Two other articles, Xu et al (2017) and Chen et al (2017), focus on crop plants and identified, respectively, an acyl transferase from rice (Oryza sativa) and an oxidoreductase from maize (Zea mays) as playing important roles in anther cuticle and wall formation and pollen viability. The importance of tapetal degeneration to pollen maturation is further underscored in two studies (Cui et al, 2017;Gao et al, 2017); they provide insight on the involvement by Cys and Asp proteases in tapetal cell death during the late stage of pollen development.…”
mentioning
confidence: 99%